Strategi Peningkatan Pendapatan Melalui Ekonomi Kreatif dan Perhitungan HPP Adaptif Sebagai Bagian dari Sektor Pariwisata di Kelurahan Salamanmloyo Kota Semarang - Puspitasari, Diana; Nur Chasanah, Amalia; Fahmi Wardhani, Masitha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Strategy for Increasing Income Through Creative Economy and Adaptive Cost of Goods Sold (COGS) Determination to Support the Tourism Sector in Salamanmloyo Urban Village The emergence of creative home-based businesses can promote income equality and growth, while also supporting global economic growth. Home-based businesses can be started with very little capital and offer flexibility because they are not tied to a physical store location or specific hours. An example of a creative home-based business that has the potential to become a leading industry in a region or area is the home-based bouquet business in the Salamanmloyo neighbourhood of Semarang City. The challenges faced by partners in general include a lack of financial literacy, which makes it difficult to determine the Cost of Goods Sold (COGS), resulting in the absence of appropriate product pricing standards and potentially hindering accurate profit calculations for their businesses in the future. The objective of the Community Service Activity is to address the issue of insufficient financial literacy in determining the Cost of Goods Sold (COGS). The methods used in this activity include education and training. The results of the community service activity show an improvement in participants' skills, as they gained additional knowledge and understanding related to bookkeeping. Participants in the training were also able to enhance their understanding and ability to create and determine the Cost of Goods Sold (COGS) for their products accurately, enabling them to accurately determine their actual profits.